2005
DOI: 10.1002/jbm.b.30484
|View full text |Cite
|
Sign up to set email alerts
|

An improved hydrophilicity via electrospinning for enhanced cell attachment and proliferation

Abstract: The wettability of electrospun poly(epsilon-caprolactone) (PCL) mats was improved by co-electrospinning with poly(vinyl alcohol) (PVA), by double-spinneret electrospinning method. The improved hydrophilicity of the hybrid PCL/PVA mats was confirmed by water contact angle measurement. The in vitro cell attachment on the hydrophobic PCL and hydrophilically modified PCL/PVA mats was compared by culture studies using human prostate epithelial cells (HPECs). The stability of water-soluble PVA component in the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
150
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(154 citation statements)
references
References 57 publications
(88 reference statements)
4
150
0
Order By: Relevance
“…The electrospinning technique is an efficient method of producing continuous and fine (micro/nano) scale fibers by drawing out the polymer solution under electrostatic forces into the whipping jets, and continuous fiber can be deposited on the conductive collector (Kim et al 2006). Electrospinningprocessing parameters such as solutions, distances between tips to collector, high-voltage supply, flow rate of injection pump and room humidity can be optimized to obtain beadless and uniform nanofibers (Chung et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The electrospinning technique is an efficient method of producing continuous and fine (micro/nano) scale fibers by drawing out the polymer solution under electrostatic forces into the whipping jets, and continuous fiber can be deposited on the conductive collector (Kim et al 2006). Electrospinningprocessing parameters such as solutions, distances between tips to collector, high-voltage supply, flow rate of injection pump and room humidity can be optimized to obtain beadless and uniform nanofibers (Chung et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies observed that PCL fibrous scaffolds caused a reduction in the ability of cell attachment, migration, proliferation, and differentiation [8]. Cell affinity towards synthetic polymer is usually poorer than natural polymer.…”
Section: -2506mentioning
confidence: 99%
“…The reason for using different biopolymers is that PCL is a biodegradable aliphatic polyester with a high strength, which is needed during artificial blood vessel implantation [11][12][13][14]. Even though electrospun PCL mats mimic the extracellular matrix in living tissues, their poor hydrophilicity decreases cell adhesion, migration, proliferation and differentiation [15]. In contrast, gelatin is a natural biopolymer derived from collagen through controlled hydrolysis.…”
Section: Introductionmentioning
confidence: 99%